2018
DOI: 10.1016/j.jphs.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide oxytocin enhances μ opioid receptor signaling as a positive allosteric modulator

Abstract: Oxytocin (OT) is a 9-amine neuropeptide that plays an essential role in mammalian labor, lactation, maternal bonding, and social affiliation. OT has been reported to exert an analgesic effect in both humans and animals, and the results of certain animal experiments have shown that the analgesic effect of OT is partially blocked by opioid receptor antagonists. To investigate the relationship between OT and μ opioid receptor (MOR), we evaluated how OT affects MOR in vitro by performing an electrical impedance-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 30 publications
2
44
1
Order By: Relevance
“…Cell culture:H EK293 cells stably expressing each of TRP channels or ORs, and HEK293A cells stably expressing GHSR were constructed in our previous reports. [46][47][48] HEK293 cells and HEK293A cells were cultured in DMEM supplemented with 10 %FBS and penicillin (100 UmL À1 )a nd streptomycin (100 mg mL À1 )a t3 78Ci nahumidified incubator (5 %C O 2 ). To maintain the stable cell lines, geneticin (flag-MOR and myc-KOR:0 .7 mg mL À1 ;G HSR:0 .8 mg mL À1 ), hygromycin (T7-DOR:0 .25 mg mL À1 ), blasticidin (TRP channels: 0.01 mg mL À1 )o rz eocin (TRP channels:0 .2 mg mL À1 )w as added to the culture medium.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…Cell culture:H EK293 cells stably expressing each of TRP channels or ORs, and HEK293A cells stably expressing GHSR were constructed in our previous reports. [46][47][48] HEK293 cells and HEK293A cells were cultured in DMEM supplemented with 10 %FBS and penicillin (100 UmL À1 )a nd streptomycin (100 mg mL À1 )a t3 78Ci nahumidified incubator (5 %C O 2 ). To maintain the stable cell lines, geneticin (flag-MOR and myc-KOR:0 .7 mg mL À1 ;G HSR:0 .8 mg mL À1 ), hygromycin (T7-DOR:0 .25 mg mL À1 ), blasticidin (TRP channels: 0.01 mg mL À1 )o rz eocin (TRP channels:0 .2 mg mL À1 )w as added to the culture medium.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…When we try to interpret the OT-PAG analgesic system, an intriguing possibility is that OT achieves an analgesic effect via mu opioid receptors, which is also a G-protein coupled metabotropic receptor whose post synaptic current can last up to minutes. A recent study found that, although OT alone does not directly bind to the opioid-binding site of mu opioid receptor, OT strongly enhances the signaling of mu opioid receptor [22]. In addition to those studies using electric stimulation of PAG, mu opioid receptor agonist injection to PAG has also confirmed the descending analgesic pathway; PAG, RVM, and SC as follows.…”
Section: Discussionmentioning
confidence: 91%
“…However, recent data shows oxytocin to significantly suppress obesity, indicating wider roles in the regulation central and systemic processes [125]. It is also of note that oxytocin is a positive allosteric modulator of the µ-opioid receptor [126], thereby linking oxytocin effects to data showing the role of the µ-opioid receptor in obesity as well as in attachment, nociception, and reward. As melatonin can regulate hypothalamic oxytocin production in rodents [127], it requires investigation as to whether variations in circadian and local melatonin production are relevant to the modulation and development of the oxytocin system in the placenta and foetus.…”
Section: Melatonin and The Opioidergic Systemmentioning
confidence: 96%